The Geography of Genius : A Search for the World's Most Creative Places from Ancient Athens to Silicon Valley - Weiner, Eric (New York Simon & Schuster Paperbacks, 2016)
Travel the world with Eric Weiner, the New York Times bestselling author of The Geography of Bliss, as he journeys from Athens to Silicon Valley-and throughout history, too-to show how creative genius flourishes in specific places at specific times. In The Geography of Genius, acclaimed travel writer Weiner sets out to examine the connection between our surroundings and our most innovative ideas. He explores the history of places, like Vienna of 1900, Renaissance Florence, ancient Athens, Song Dynasty Hangzhou, and Silicon Valley, to show how certain urban settings are conducive to ingenuity. And, with his trademark insightful humour, he walks the same paths as the geniuses who flourished in these settings to see if the spirit of what inspired figures like Socrates, Michelangelo, and Leonardo remains. In these places, Weiner asks, What was in the air, and can we bottle it? This link can be traced back through history: Darwin's theory of evolution gelled while he was riding in a carriage. Freud did his best thinking at this favourite coffee house. Beethoven, like many geniuses, preferred long walks in the woods. Sharp and provocative, The Geography of Genius redefines the argument about how genius came to be. His evaluation of the importance of culture in nurturing creativity is an informed romp through history.
Include Bibliography and Index.
Keywords: Voyages and travels -- Genius -- Travel